Mitigation Strategies in Supply Chain Risk Management: A Literature Review - Hudin, Norlaile Salleh; Ayoup, Hazeline; Habidin, Nurul Fadly; Surya, Priadi; Hussin, Kasmaruddin Che (CENTRAL ASIA AND THE CAUCASUS, 2021)
This systematic literature review aims to analyze risk mitigation studies spanning across 2004 –2019. Embarking on the PRISMA approach, studies were selected through the identification, screening, eligibility and analysis steps. The findings revealed three main themes (culture, independent response and co-operative response), and 16 sub- themes. Several recommendations for future research were underscored including the need to conduct more studies to understand the culture, independent response and co- operative response for reactive strategies. This study could guide future researchers to augment the current literature by progressing towards the proposed recommendations.